How Innovative Is Your Company's Culture? - Prabhu, Jaideep; Tellis, Gerard; Dodgson, Mark; Danneels, Erwin; Scharmer, Claus Otto 1961-; Weintraub, Joseph; Rao, Jay (MIT Sloan Management Review, 2013)
Everyone wants an innovative corporate culture, but how do you develop one? Prior research has suggested that the degree to which a company is innovative depends much less on capital, geography or sector than on the company's culture. The authors of this article say that the ability of a culture to support innovation depends on six key building blocks. They developed an assessment tool based on these building blocks, which can be used by managers to help make their culture more conducive to innovation. The authors say the six basic building blocks of an innovative corporate culture are values, behaviors, climate, resources, processes and success. Values drive priorities and decisions, which are reflected in how a company spends its time and money. Behaviors involve how people act in the cause of innovation. Climate is the tenor of workplace life. An innovative climate cultivates enthusiasm, challenges people to take risks within a safe environment, fosters learning and encourages independent thinking. Resources are comprised of three main factors: people, systems and projects. Of these, people -- especially "innovation champions" -- are the most critical, because they have a powerful impact on the company's values and climate. Processes are the routes innovations follow as they are developed. Finally, the internal and external success of an innovation drives many actions and decisions that may have an impact on the next one: who will be rewarded, which people will be hired and which projects will get the green light. After exploring this framework, the authors offer examples of companies that exemplify each quality. They also include a 54-element test they developed to enable managers to assess a company's "Innovation Quotient." Over the past three years, more than 1,000 employees in 15 companies around the world have taken this assessment. The authors give examples of companies that have implemented changes to make their culture more innovative based on what they learned from the survey, and a case study outlines the experience of a Latin American company with the assessment tool.
Keywords: Creative ability in business; Creative thinking; Technological innovations; New products; Créativité dans les affaires; Innovations